Efficacy of non-invasive positive pressure ventilation in the treatment of respiratory failure in patients with COPD at the acute exacerbation stage - De-Peng Li (Journal of Hainan Medical University, 2016)
Objective: To observe the efficacy of non-invasive positive pressure ventilation (NIPPV) in the treatment of respiratory failure in patients with COPD at the acute exacerbation stage. Methods: A total of 38 COPD patients at the acute exacerbation stage with respiratory failure who were admitted in our hospital from January, 2012 to January, 2013 with complete medical materials were included in the study and divided into the observation group and the control group according to different treatment methods. On admission, the patients in the two groups were given oxygen inhalation, positive infection control, and drugs that could improve the respiratory function. On the basis, the patients in the observation group were given additional NIPPV. The improvement of blood gas indicators 4, 24, 72 d after admission, and 5, 30 d after discharge in the two groups was compared. The hospitalization time and the number of second hospitalization within 3 months in the two groups were compared. Results: In the observation group, pH value after 4 h ventilation was significantly elevated, and maintained at a stable state after 24 h ventilation, while in the control group, the change of pH value was not statistically significant, and after 5 d treatment, pH value was yet low. In the observation group, PaCO2 was significantly reduced in a short ventilation time, while in the control group, the descending range was small. The comparison of pH and PaCO2 4 h, 24 h, 72 h, and 5 d after treatment between the two groups was statistically significant, but PaCO2 in the two groups could not reduce to the normal level. PaO2 after treatment in the two groups was improved, but the improved degree in the observation degree was significantly superior to that in the control group. The comparison of blood gas indicators 30 d after discharge between the two groups was not statistically significant. The hospitalization time in the observation group was shortened, and the number of second hospitalization within 3 months was significantly lower than that in the control group. Conclusions: NIPPV can rapidly correct the respiratory failure state in patients with COPD merged with respiratory failure, improve the pulmonary function, and reduce the lung injury, with an accurate efficacy.